2014
DOI: 10.1002/jcp.24575
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐18 Has Antipermeablity and Antiangiogenic Activities in the Eye: Reciprocal Suppression With VEGF

Abstract: Interleukin-18 (IL-18) is increased along with IL-1β by activation of the inflammasome and has been implicated in inflammatory and autoimmune diseases, but its role in the eye is uncertain. In patients with macular edema due to retinal vein occlusion, intraocular IL-18 levels increased significantly (p<0.001) after treatment with ranibizumab particularly in patients with high baseline IL-18 which correlated with good visual outcome (p<0.05). In mice with ischemic retinopathy, suppression of VEGF caused an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 48 publications
0
41
1
Order By: Relevance
“…Our data pertaining to a role for IL-18 in regulating neovascularization was supported by independent reports in the literature, 10,11 and strongly indicated that IL-18 could have some therapeutic benefit in neovascular AMD, in contrast to a report by Ambati et al 12 Human IL-18 (SB-485232, GSK) is a clinically enabled investigational drug that has been injected systemically in >170 cancer patients with an excellent safety profile, with numerous on-going studies. 13,14 We sought to examine the tolerability and efficacy of SB-485232 in a nonhuman primate model of neovascular AMD.…”
Section: Mature Il-18 Is Safe and Reduces Development Of Laser-inducecontrasting
confidence: 53%
“…Our data pertaining to a role for IL-18 in regulating neovascularization was supported by independent reports in the literature, 10,11 and strongly indicated that IL-18 could have some therapeutic benefit in neovascular AMD, in contrast to a report by Ambati et al 12 Human IL-18 (SB-485232, GSK) is a clinically enabled investigational drug that has been injected systemically in >170 cancer patients with an excellent safety profile, with numerous on-going studies. 13,14 We sought to examine the tolerability and efficacy of SB-485232 in a nonhuman primate model of neovascular AMD.…”
Section: Mature Il-18 Is Safe and Reduces Development Of Laser-inducecontrasting
confidence: 53%
“…The exact role of IL-18 in the eye is still unclear, 51 but VEGF and IL-18 were shown to suppress each other's production. 52 In a mouse model of neovascularization, 53 IL-18 inhibited new vessel formation but promoted damage to the RPE that mimics aspects of the dry form of AMD. 54 Alteration of RPE cells after mast cell degranulation could thus be at least in part related to IL-18 increase.…”
Section: And In Retinalmentioning
confidence: 98%
“…41 So far, a series of previous studies have investigated the role of IL-18 in the physiological and pathological angiogenesis. For instance, in mice with ischemic retinopathy, intraocular injection of IL-18 suppresses leakage and neovascularization caused by vascular endothelial growth factor, 42 suggesting that IL-18 inhibits vascular endothelial growth factor-dependent induction of proangiogenic status. On the other hand, IL-18 promotes migration and tube formation by human microvascular endothelial cells in vitro, indicating its pro-angiogenic property.…”
Section: Discussionmentioning
confidence: 99%